Synthesis, Analgesic and Antimicrobial Activities of Some Novel Isoxazole Derivatives - Sahu, SK; Banerjee, M; Sahu, D; Behera, CC; Pradhan, GC; Azam, Md Afzal (Dhaka University Journal of Pharmaceutical Sciences, 2009)
Substituted aryl-N-chalconyl aminophenols 1a-f were synthesized by base catalysed condensation of equimolar mixture of N-(4-hydroxyphenyl)-acetamide and appropriate araldehydes. Treatment of compounds 1a-f with hydroxylamine hydrochloride in ethanol afforded a series of novel 4-(5â²-substituted-aryl-4â²,5â²-dihydro-isoxazole-3â²-yl-amino) phenols have been synthesized by treating substituted aryl-N-chalconyl aminophenol with hydroxylamine hydrochloride. Structures of newly synthesized compounds 2a-f were confirmed by IR, 1H-NMR and elemental analysis data. The synthesized compounds were investigated for their analgesic and antimicrobial activities. Compounds 2e and 2f exhibited significant analgesic activity in comparison to the reference drug paracetamol. In in vitro anti-microbial screening, compounds 2c and 2f showed higher antibacterial and antifungal activity in comparison to the reference standard ciprofloxacin and clotrimazole, respectively. Compound 2f bearing 4-Cl phenyl substitution at 5 position of Ioxazoline ring was found to be the most potent compound of the series. Key words: Isoxazole, Analgesic, Antibacterial activity. doi: 10.3329/dujps.v7i2.2165 Dhaka Univ. J. Pharm. Sci. 7(2): 113-118, 2008 (December)